Preliminaries - RAMOS HOLGUÍN, BERTHA; Peñaloza Rallón, Anna Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This section includes the main information about the journal, editorial committee and collaborators, and table of contents.